Differentiated Instruction through Tiered Activities in Teaching Geometry to the Junior High School students (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A study of differentiated instruction through tiered activities in teaching Geometry was conducted using a quasi-experimental method with pre-post-tests control group design to measure the effectiveness of differentiated instruction in teaching geometry. Formed two intact groups, and seventy-six (76) Junior high school students were selected as respondents of the study. Thirty-eight (38) belong to the control group, and the remaining thirty-eight (38) belong to the experimental. Students in experimental were exposed to different strategies in differentiated instruction through tiered activities in which the degree of complexity or abstractedness differs. On the other hand, students in the control group were exposed to traditional instructions. The findings revealed that the overall performance of the experimental group is above the 75% level of criterion. It is also revealed a significant increase in the performance of the experimental and control groups from pre-test to post-test. It is concluded that traditional and differentiated instruction are both effective approaches in the teaching and learning process, and teachers should use various teaching approaches to address todays’ diverse learners. Moreover, it is suggested not to use a single strategy, method, approach, or technique in delivering instruction to address the need of todays’ mixed-ability classroom. It is recommended to include differentiated instruction as approach in the In-Service Training of the teachers and conduct a series of seminars on the different elements of this approach to have a deeper understanding and have a better idea of how to use it to determine its actual effect on students’ achievement.